Beginning C# 2008 Objects From Concept to Code - Palmer, Grant; Barker, Ken (Apress : Imprint: Apress, 2009)
Updated with the changes to C#, Beginning C# 2008 Objects: From Concepts to Code introduces complete beginners to C# coding practice with a solid methodological foundation written by two critically-acclaimed experts in the field, already authors of the best-selling Beginning C# Objects. By building from first principles in object-oriented terminology, then advancing through application design with Unified Modeling Language (UML) into practical examples, Beginning C# 2008 Objects: From Concepts to Code provides a foundational guide written from the perspective of two experienced, working authorities on C#. Working coders will benefit from the object-oriented cast of the book and its section on use-case modeling. This is the book to read if you want to deepen and advance your existing professional development in C# with an eye towards advancing out of pure coding work. For the reader wishing to "simply learn C#", this book will provide exactly that. In addition to listing code and syntax, Beginning C# 2008 Objects: From Concepts to Code also walks you through the design and architecting of a functioning C# application, showing the "why" and the "how" of the development decisions that go into professional C# coding.